P275 Biological therapies for patients with Crohn's disease: More options mean less surgical interventions. (15th January 2020) - Chin, Y F; PUJJI, O; Wilkinson, B; Mohan, S; Nnaji, M; Yassin, N
Abstract: Background: The advent of biologic therapy and their acceptance into mainstream use for the medical management of patients with inflammatory bowel disease (IBD) has transformed the landscape of treatment for this condition. It has particularly become a mainstay in the treatment of fistulating or perianal Crohn's Disease (CD). Data have shown that overall, 70% of patients will require surgical resections for CD. Consequently, questions have endured regarding the effect of biologic medications on the overall treatment course of CD patients. Our aim is to identify the efficacy of biologics by measuring surgical free survival. We subcategorised the period into 3 categories, including periods less than a year 1–5 years and >5 years and comparing these with the number of biologics they required to be switched either due to side effects or loss of medical response. Methods: A retrospective analysis of prospectively collected data was correlated with the clinical coding department, inflammatory bowel disease and surgical databases. Patients receiving biological therapies were identified (Infliximab, Adalimumab, Vedolizumab, Ustekinumab, Certolizumab). Demographics, clinical and surgical data were analysed. Results: Sixty-six patients were included in our analysis. Male to female ratio is 1 to 1.07, age range was 18–77, median age 41 (SD:17.46) years old. Twenty-five patients had ileocaecal resection, 17 had hemi and segmental colectomy, 7 had small bowel resection, 10 had subtotal colectomy and 7 had panproctocolectomy. Refractory to one biologic does not indicate biological failure; number of biologics switched and surgical free survival were compared. We have utilised the Spearman correlation coefficient for nominal analysis which gave us a coefficient of +0.725, p = 0.00. This indicates that both factors have a strong positive correlation between numbers of biologics patients used against period required for surgical management. Conclusion: In the current era of biological therapies, with a breadth of choice of therapeutic agents, our data has a positive correlation between the number of biological agents used and surgery-free survival for patients with Crohn's disease. A multidisciplinary approach to the management of these patients should be personalised, and suitability to each biological agent should be considered in addition to close surgical observation.